Rubber compositions based on highly saturated elastomers and butadiene-styrene copolymers
Patent Information
- Application Number
- CN202280040917.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-06-07
- Filing Date
- 2022-05-30
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-05-30
Smart Images

Figure QLYQS_1 
Figure BDA0004593223980000051 
Figure BDA0004593223980000131
Abstract
Description
Technical Field
[0001] This invention relates to a conveyor belt with improved mechanical properties. Background Technology
[0002] A conveyor belt (also known as a transport belt or conveyor belt) is essentially composed of a looped belt and is typically supported and driven by electric pulleys. Therefore, it is capable of transporting materials or goods over relatively long distances (which can extend up to several kilometers).
[0003] In the mining industry (especially quarries), conveyor belts are needed to receive large quantities of ore, pebbles, rocks, etc., often in a rough manner. Therefore, they must possess excellent mechanical properties for as long as possible to maximize their service life. Elongation at break is a particularly important mechanical property to account for the deformation the conveyor belt undergoes when receiving heavy loads (such as rocks) that may have sharp indentations.
[0004] Therefore, it is important to have conveyor belts whose rubber composition possesses good mechanical properties, particularly elongation at break. It is also desirable to maintain these mechanical properties for as long as possible to extend the service life of these conveyor belts.
[0005] For this purpose, document WO 2017 / 019235 A1 proposes a rubber composition for conveyor belts, the rubber composition being based on a mixture of styrene-butadiene rubber (SBR) and EPDM (ethylene-propylene-diene monomer) rubber.
[0006] In addition, conveyor belts must meet other requirements, such as good abrasion resistance and good crack propagation resistance. Like maintaining mechanical properties, these two properties extend the service life of conveyor belts containing rubber compositions.
[0007] However, it remains advantageous for manufacturers to have compositions that can further improve the aforementioned performance trade-offs, thereby obtaining conveyor belts with the longest possible service life. Summary of the Invention
[0008] During further research, the applicant unexpectedly discovered that a combination of styrene-butadiene rubber and a specific elastomer based on ethylene and 1,3-diene could improve the aforementioned performance trade-off, with the ethylene units in the copolymer accounting for more than 50 moles of the monomer units in the copolymer.
[0009] Therefore, one subject of the present invention is a rubber composition based at least on 10 phr to 90 phr of styrene-butadiene rubber (SBR) and 10 phr to 90 phr of a copolymer of ethylene and 1,3-diene, fillers and crosslinking system, wherein the ethylene units in the copolymer of ethylene and 1,3-diene account for more than 50 mol% of the monomer units of the copolymer of ethylene and 1,3-diene, and the rubber composition has a good performance trade-off between crack propagation resistance and elongation at break.
[0010] The present invention also relates to a rubber article comprising a composition according to the invention, particularly a conveyor belt comprising a rubber composition according to the invention.
[0011] I-Definition
[0012] The expression “based on” used to define the composition of a catalytic system or composition is understood to mean a mixture of these components, or the products of the reaction of some or all of these components with each other at least partially during various stages of the production of the catalytic system or composition. In the case of a composition, the composition may thus be in a fully or partially crosslinked state, or in a non-crosslinked state.
[0013] "Elastomer matrix" is understood to mean all elastomers in the composition, including copolymers of ethylene and 1,3-diene as defined below.
[0014] Within the meaning of this invention, the expression "parts by weight / hundred parts by weight elastomer" (or phr) should be understood to mean the weight percentage of elastomer present in each hundred parts of the rubber composition under consideration.
[0015] In this document, all percentages (%) shown are weight percentages (%) unless otherwise explicitly stated.
[0016] Furthermore, any numerical interval expressed as "between a and b" represents a range of values greater than a and less than b (i.e., excluding the limits a and b), while any numerical interval expressed as "from a to b" means a range of values from a to b (i.e., including the strict limits a and b). In this application, when a numerical interval is expressed as "from a to b," it is also preferable to express the interval expressed as "between a and b."
[0017] When referring to a "major" compound, for the purposes of this invention, it is understood to mean that among compounds of the same type in the composition, this compound is dominant, i.e., it is the compound that accounts for the largest amount by weight among compounds of the same type. Thus, for example, a dominant elastomer is the elastomer that accounts for the largest weight relative to the total weight of elastomers in the composition. Similarly, a "major" filler is the filler that accounts for the largest weight among the fillers in the composition. For example, in a system containing only one elastomer, said elastomer is dominant for the purposes of this invention, and in a system containing two elastomers, the dominant elastomer accounts for more than half the weight of the elastomer. Conversely, a "minor" compound is a compound that does not account for the largest weight fraction among compounds of the same type. Preferably, the term "major" is understood to mean present at a concentration greater than 50%, preferably greater than 60%, 70%, 80%, or 90%, and more preferably, the "major" compound accounts for 100%.
[0018] In this application, the expression "all monomer units of the copolymer" or "total amount of monomer units of the copolymer" means all repeating units of the copolymer produced by inserting monomers into the polymer chain through polymerization. Unless otherwise stated, the content of monomer units or repeating units in copolymers of ethylene and 1,3-diene is given as a molar percentage calculated based on all monomer units of the copolymer.
[0019] The compounds mentioned in the specification may be fossil-derived compounds or bio-based compounds. In the case of bio-based compounds, they may be partially or wholly derived from biomass or obtained from renewable starting materials derived from biomass. Similarly, the mentioned compounds may also be derived from the recycling of previously used materials, i.e., they may be partially or wholly derived from a recycling process or obtained from starting materials that are themselves derived from a recycling process. This particularly includes polymers, plasticizers, fillers, etc.
[0020] Unless otherwise stated, all glass transition temperatures “Tg” values described herein are measured in a known manner by DSC (differential scanning calorimetry) in accordance with standard ASTM D3418 (1999). Attached Figure Description
[0021] II - Brief Description of the Attached Figures
[0022] [ Figure 1 ] Figure 1 A cross-sectional view of the conveyor belt is shown. Detailed Implementation
[0023] III - Description of the Invention
[0024] III-1 Elastomer Matrix
[0025] The essential characteristic of the rubber composition according to the invention is that it comprises 10 phr to 90 phr of styrene-butadiene rubber (SBR) and 90 phr to 10 phr of a copolymer of ethylene and 1,3-diene, wherein the ethylene units in the copolymer account for more than 50 mol% of the monomer units of the copolymer. In this application, for the sake of brevity, "a copolymer of ethylene and 1,3-diene, wherein the ethylene units in the copolymer account for more than 50 mol% of the monomer units of the copolymer" can be expressed as "a copolymer of ethylene and 1,3-diene".
[0026] It should be noted that SBR can be prepared in emulsion (ESBR) or solution (SSBR). Among the SBRs that can be used in the context of this invention, those with a styrene content between 5% and 60% by weight, more particularly between 20% and 50%, a butadiene moiety 1,2-bond content (mol%) between 4% and 75%, and a trans-1,4-bond content (mol%) between 10% and 80% are particularly noteworthy. Advantageously, styrene-butadiene rubber is an SBR with a styrene content relative to the total weight of the copolymer between 5% and 60% by weight, preferably between 6% and 30% by weight, and a butadiene moiety 1,2-bond content (mol%) between 4% and 75%, preferably between 15% and 30%. In the context of this invention, for example, “KER1502” SBR from Synthos can be used.
[0027] Advantageously, the number-average molar mass (Mn) of the styrene-butadiene rubber is in the range of 40,000 g / mol to 400,000 g / mol, preferably 50,000 g / mol to 250,000 g / mol.
[0028] SBR can be composed of a mixture of styrene-butadiene rubbers with different microstructures and / or macrostructures.
[0029] "Copolymers of ethylene and 1,3-diene" is understood to mean any copolymer whose monomer units are produced by the polymerization of ethylene and 1,3-diene. Therefore, copolymers of ethylene and 1,3-diene are produced solely by the polymerization of ethylene monomers and 1,3-diene monomers.
[0030] In a known manner, the term "ethylene unit" refers to the -(CH2-CH2)- unit obtained by inserting ethylene into an elastomer chain.
[0031] In a known manner, the term "1,3-diene unit" means a unit obtained by inserting 1,3-diene via 1,4-addition, 1,2-addition or 3,4-addition (in the case of isoprene). The 1,3-diene unit is, for example, 1,3-diene or a mixture of 1,3-dienes, a 1,3-diene having 4 to 12 carbon atoms, for example very particularly 1,3-butadiene and isoprene. Preferably, the 1,3-diene is 1,3-butadiene.
[0032] Advantageously, the ethylene units in the copolymer of ethylene and 1,3-diene account for between 50 mol% and 95 mol%, preferably between 55 mol% and 90 mol% of the monomer units of the copolymer.
[0033] The copolymer of ethylene and 1,3-diene advantageously comprises units of formula (I) and / or (II). The presence of the saturated six-membered ring unit (1,2-cyclohexanediyl) of formula (I) as a monomer unit in the copolymer may result from a series of very specific insertions of ethylene and 1,3-butadiene into the polymer chain during the growth process of the polymer chain.
[0034]
[0035] -CH2-CH(CH=CH2)-(II)
[0036] For example, the copolymer of ethylene and 1,3-diene may be free of units of formula (I). In this case, it preferably comprises units of formula (II).
[0037] When the copolymer of ethylene and 1,3-diene comprises units of formula (I), or units of formula (II), or units of formula (I) and units of formula (II), the mole percentages (o and p respectively) of the units of formula (I) and the units of formula (II) in the copolymer preferably satisfy the following equation (Equation 1), more preferably satisfy the equation (Equation 2), where o and p are calculated based on all monomer units of the copolymer.
[0038] 0<o+p≤25 (Equation 1)
[0039] 0<o+p<20 (Equation 2)
[0040] Also advantageously, the copolymer of ethylene and 1,3-diene has a crystallinity of less than 20%, more advantageously less than 15%, even more advantageously less than 10%. The techniques for determining the mole fraction, average molar mass (Mn), glass transition temperature and crystallinity are described in the Examples hereinafter.
[0041] According to the present invention, the copolymer of ethylene and 1,3-diene (preferably 1,3-butadiene) is a random copolymer.
[0042] Advantageously, the number-average mass (Mn) of the copolymer of ethylene and 1,3-diene (preferably a copolymer of ethylene and 1,3-diene (preferably 1,3-butadiene) is in the range of 100,000 g / mol to 300,000 g / mol, preferably 150,000 g / mol to 250,000 g / mol.
[0043] Copolymers of ethylene and 1,3-diene can be obtained, particularly based on the target microstructure of the copolymer, according to various synthetic methods known to those skilled in the art. Typically, they can be prepared, particularly in the presence of a catalytic system containing a metallocene complex, via the copolymerization of at least one 1,3-diene (preferably 1,3-butadiene) and ethylene using known synthetic methods. Regarding the catalytic system, the metallocene-based catalytic systems described in EP 1092731, WO 2004 / 035639, WO 2007 / 054223, and WO2007 / 054224 under the applicant's name can be mentioned. Copolymers of ethylene and 1,3-diene (including when they are random elastomers) can also be prepared by using pre-formed catalytic systems (e.g., those described in documents WO 2017 / 093654 A1, WO 2018 / 020122 A1, and WO 2018 / 020123 A1).
[0044] Copolymers of ethylene and 1,3-diene can consist of a mixture of copolymers of ethylene and 1,3-diene with different microstructures and / or macrostructures.
[0045] Advantageously, the styrene-butadiene rubber content in the composition according to the invention is in the range of 20 phr to 80 phr, preferably 30 phr to 70 phr, and the content of the copolymer of ethylene and 1,3-diene in the composition according to the invention is in the range of 20 phr to 80 phr, preferably 30 phr to 70 phr. Advantageously, the sum of the content of the copolymer of ethylene and 1,3-diene and the content of styrene-butadiene rubber is greater than 50 phr, preferably greater than 75 phr, more preferably greater than 90 phr. Advantageously, the styrene-butadiene rubber and the copolymer of ethylene and 1,3-diene are the only elastomers in the composition, i.e., their content in the composition is 100 phr.
[0046] The elastomer matrix can advantageously contain only styrene-butadiene rubber and copolymers of ethylene and 1,3-diene as elastomers.
[0047] The elastomeric matrix of the compositions according to the invention may alternatively also contain diene elastomers (also referred to herein as "other elastomers") other than styrene-butadiene rubber and copolymers of ethylene and 1,3-diene.
[0048] Other elastomers in the elastomer matrix of the tire according to the invention are preferably selected from highly unsaturated diene elastomers, such as polybutadiene (abbreviated as "BR"), synthetic polyisoprene (IR), natural rubber (NR), butadiene copolymers other than SBR, isoprene copolymers, and mixtures of these elastomers. "Highly unsaturated diene elastomer" is generally understood to mean a diene elastomer that is at least partially derived from conjugated diene monomers and has a diene source (conjugated diene) unit content greater than 50% (mol%).
[0049] The content of other elastomers in the compositions according to the invention can range from 0 phr to 20 phr, preferably from 0 phr to 10 phr, and more preferably from 0 phr to 5 phr. More preferably, the elastomer matrix does not contain any elastomers other than styrene-butadiene rubber and copolymers of ethylene and 1,3-diene, i.e., the level of other elastomers is 0 phr.
[0050] III-2 packing
[0051] A key feature of the composition according to the invention is that it is based on reinforcing fillers.
[0052] As examples of reinforcing fillers known to those skilled in the art, carbon black or reinforcing inorganic fillers (e.g., silica in the presence of a coupling agent), or blends of both types of fillers, will be specifically mentioned. Indeed, silica is known to be a reinforcing filler in the presence of a coupling agent capable of binding it to the elastomer. Preferably, the weight-average size of the reinforcing filler is less than 500 nm, particularly between 20 nm and 200 nm.
[0053] According to the invention, the reinforcing filler advantageously comprises carbon black, silica, or a mixture thereof. Preferably, the reinforcing filler comprises more than 50% by weight, more preferably more than 80% by weight, of carbon black. More preferably, the reinforcing filler consists solely of carbon black, i.e., carbon black constitutes 100% by weight of the reinforcing filler.
[0054] Suitable carbon blacks include all carbon blacks, particularly those commonly used in tires or their treads. Of particular interest will be made of reinforcing carbon blacks of the 100, 200, and 300 series, or carbon blacks of the 500, 600, or 700 series (ASTM D-1765-2017 grade), such as N115, N134, N234, N326, N330, N339, N347, N375, N550, N683, and N772. These carbon blacks may be used commercially available in their standalone state, or in any other form (e.g., as a carrier for some rubber additives used). Carbon blacks may, for example, be incorporated into diene elastomers (particularly isoprene elastomers) in masterbatch form (see, for example, patent applications WO97 / 36724-A2 or WO99 / 16600-A1).
[0055] In the aforementioned carbon black, the BET specific surface area is 60 m². 2 / g to 160m 2 Carbon black in the range of / g is particularly preferred.
[0056] Therefore, preferably, the reinforcing filler contains more than 50% by weight, preferably more than 80% by weight, of at least one carbon black, said carbon black having a BET specific surface area of 60 m². 2 / g to 160m 2 / g, preferably 70m 2 / g to 130m 2 / g, preferably 100m 2 / g to 120m 2 Within the range of / g. Measure the BET specific surface area of carbon black according to standard ASTM D6556-10 [multi-point (at least 5 points) method - gas: nitrogen - relative pressure p / p0 range: 0.1 to 0.3].
[0057] Suitable silica includes any type of precipitated silica, particularly highly dispersible precipitated silica (referred to as "HDS," used to denote "highly dispersible" or "highly dispersible silica"). These precipitated silicas (which may or may not be highly dispersible precipitated silica) are well known to those skilled in the art. For example, references may be made to the silica described in applications WO03 / 016215-A1 and WO03 / 016387-A1. In commercially available HDS silica, silica from Evonik may be used in particular. 5000GR and 7000GR silica, or from Solvay 1085GR 1115MP 1165MP Premium 200MP and HRS1200MP silica. As a non-HDS silica, the following commercial silica can be used: from Evonik... VN2GR and VN3GR silica, from Solvay 175GR silica, or Hi-Sil EZ120G(-D), Hi-Sil EZ160G(-D), Hi-Sil EZ200G(-D), Hi-Sil243LD, Hi-Sil 210 and Hi-Sil HDP 320G silica from PPG.
[0058] To couple silica to a diene elastomer, a coupling agent (or binder) that is at least bifunctional can be used in a known manner to provide a satisfactory chemical and / or physical connection between the inorganic filler (its particulate surface) and the diene elastomer. In particular, at least bifunctional organosilanes or polyorganosiloxanes are used. "Bifunctional" is understood to mean a compound having a first functional group capable of interacting with the inorganic filler and a second functional group capable of interacting with the diene elastomer. For example, such a bifunctional compound may contain a first functional group containing silicon atoms and a second functional group containing sulfur atoms, the first functional group being capable of interacting with the hydroxyl groups of the inorganic filler and the second functional group being capable of interacting with the diene elastomer.
[0059] Preferably, when used, the organosilane is selected from (symmetric or asymmetric) organosilane polysulfides (e.g., bis(3-triethoxysilylpropyl)tetrasulfide (abbreviated TESPT) sold by Evonik under the name Si69, or bis(triethoxysilylpropyl)disulfide (abbreviated TESPD) sold by Evonik under the name Si75), polyorganosiloxanes, mercaptosilanes, and terminal mercaptosilanes (e.g., S-(3-(triethoxysilyl)propyl)octanethioate sold by Momentive under the name NXT Silane). More preferably, the organosilane is an organosilane polysulfide.
[0060] When using reagents for coupling silica to elastomers, those skilled in the art can readily adjust the content of the coupling agent. Typically, the content of the coupling agent is from 0.5% to 15% by weight relative to the amount of silica.
[0061] Those skilled in the art can readily adjust the content of reinforcing filler according to the intended use of the rubber composition. Advantageously, the content of reinforcing filler in the compositions according to the invention is in the range of 10 phr to less than 100 phr, preferably 15 phr to 90 phr, more preferably 20 phr to 75 phr. More particularly, the content of reinforcing filler in the compositions according to the invention is in the range of 10 phr to less than 49 phr, preferably 15 phr to 48 phr, more preferably 20 phr to 47 phr.
[0062] Advantageously, the volume fraction of filler in the composition according to the invention is less than 19%, preferably from 10% to less than 19%, more preferably from 11% to 18%, and more preferably from 12% to 17%. The volume fraction of filler in the rubber composition is defined as the ratio of the volume of filler to the volume of all components of the composition. It should be understood that the volume of all components is calculated by summing the volumes of each component of the composition.
[0063] III-3 crosslinking system
[0064] The crosslinking system can be any type of system known to those skilled in the art of tire rubber compositions. The crosslinking system may be particularly based on sulfur and / or peroxides and / or bismaleimides.
[0065] Preferably, the crosslinking system is based on sulfur; it is then referred to as a vulcanization system. Sulfur can be provided in any form (particularly molecular sulfur and / or at least one sulfur-donating agent). It is also preferred that at least one vulcanization accelerator is present, and optionally, and even more preferably, various known vulcanization activators or known vulcanization retarders can be used, such as zinc oxide, stearic acid or equivalent compounds (e.g., stearates) and transition metal salts, guanidine derivatives (particularly diphenylguanidine).
[0066] The sulfur content is preferably between 0.5 phr and 12 phr, particularly between 1 phr and 10 phr. The vulcanization accelerator is preferably between 0.5 phr and 10 phr, more preferably between 0.5 phr and 5.0 phr.
[0067] As accelerators, any compound capable of acting as a vulcanization accelerator for diene elastomers in the presence of sulfur can be used, particularly thiazole-type accelerators and their derivatives, or accelerators of the sulfenamide, thiuram, dithiocarbamate, dithiophosphate, thiourea, and xanthate types. Examples of such accelerators include, in particular, the following compounds: 2-mercaptobenzothiazole disulfide (abbreviated “MBTS”), N-cyclohexyl-2-benzothiazole sulfenamide (“CBS”), N,N-dicyclohexyl-2-benzothiazole sulfenamide (“DCBS”), N-(tert-butyl)-2-benzothiazole sulfenamide (“TBBS”), N-(tert-butyl)-2-benzothiazole sulfenimide (“TBSI”), tetrabenzylthiuram disulfide (“TBZTD”), zinc dibenzyl dithiazolecarbamate (“ZBEC”), and mixtures of these compounds.
[0068] III-4 Plasticizing System
[0069] The rubber compositions according to the invention may contain a plasticizing system, but this is not mandatory.
[0070] For example, the rubber composition of the conveyor belt may not contain any plasticizer that is liquid at 23°C, or may contain less than 40 phr, preferably less than 30 phr, of plasticizer that is liquid at 23°C.
[0071] Advantageously, the rubber composition of the conveyor belt contains a plasticizer that is liquid at 23°C, preferably in a content of 0 phr to less than 40 phr, more preferably 2 phr to 30 phr, and more preferably 3 phr to 20 phr.
[0072] Plasticizers that are liquid at 23°C can be selected from naphthenic oils (low or high viscosity, especially hydrogenated or non-hydrogenated), paraffinic oils, MES oils, TDAE oils, RAE oils, TRAE oils, SRAE oils, mineral oils, vegetable oils, ether plasticizers, ester plasticizers, phosphate ester plasticizers, sulfonate plasticizers, and mixtures thereof. Advantageously, plasticizers that are liquid at 23°C are selected from MES oils, TDAE oils, naphthenic oils, vegetable oils, and mixtures thereof.
[0073] Liquid plasticizers are referred to as "low Tg", meaning that their Tg is preferably below -20°C, and more preferably below -40°C.
[0074] Furthermore, the rubber composition preferably does not contain any hydrocarbon plasticizer (or plasticizer resin), or contains less than 10 phr, preferably less than 5 phr, of hydrocarbon plasticizer resin. In a particularly advantageous manner, the rubber composition does not contain any hydrocarbon plasticizer resin. The term "resin" is a compound known to those skilled in the art to be solid at ambient temperature (23°C), which differs from liquid plasticizer compounds (e.g., oils). Plasticizer resins have been described, for example, in the article entitled "Hydrocarbon Resins" by R. Mildenberg, M. Zander, and G. Collin (New York, VCH, 1997, ISBN 3-527-28617-9), Chapter 5 of which relates to their applications, particularly in the field of tire rubber (5.5. "Rubber Tires and Mechanical Goods").
[0075] III-5 Possible Additives
[0076] The rubber composition according to the invention may optionally contain all or part of common additives typically used in elastomer compositions (e.g., elastomer compositions for conveyor belts), such as protective agents (e.g., anti-ozone waxes, chemical anti-ozone agents, antioxidants), anti-fatigue agents, etc.
[0077] III-6 Rubber Products
[0078] Another subject of the present invention is rubber articles comprising compositions according to the present invention.
[0079] Considering the improved performance trade-offs within the context of this invention, rubber articles are advantageously selected from pneumatic tires, non-pneumatic tires, tracks, and conveyor belts.
[0080] More specifically, the present invention relates to a conveyor belt comprising a rubber composition according to the invention. The conveyor belt can be any type of conveyor belt comprising the rubber composition.
[0081] In a simplified way, refer to Figure 1 The conveyor belt (1) includes a support layer (2), a reinforcement layer (3), and a drive layer (4). Typically, the reinforcement layer (3) is located between the support layer (2) and the drive layer (4).
[0082] A conveyor belt load-bearing layer can be defined as the layer on which the conveyor belt receives various types of loads (e.g., consumer goods, materials such as rocks, pebbles, or ores). A conveyor belt reinforcement layer can be defined as the layer used to reinforce the conveyor belt, particularly by limiting its deformation. A conveyor belt drive layer (also known as a pulley cover layer) can be defined as the layer driven by any mechanical device (e.g., motorized gears or pulleys).
[0083] The reinforcing layer (3) may include a plurality of steel reinforcing elements (5) (e.g., steel cables) embedded in an elastomeric matrix (6) of the reinforcing layer (3). Alternatively, the reinforcing layer (3) may consist of one or more fabric reinforcing layers (not shown).
[0084] The conveyor belt (1) may also include one or more other layers, which may be located between the support layer (2) and the reinforcement layer (4) and / or between the reinforcement layer (3) and the drive layer (4).
[0085] The compositions according to the invention are particularly suitable for constituting the carrier layer (2) of a conveyor belt (1).
[0086] Therefore, the conveyor belt (1) preferably includes at least one load-bearing layer (2), a reinforcing layer (3) and a drive layer (4), wherein the load-bearing layer (2) is composed of a rubber composition according to the invention.
[0087] Another specific subject of the invention is an inflatable or non-pneumatic tire having a tread comprising a composition according to the invention.
[0088] The tread has a tread surface with a tread pattern formed by multiple grooves. These grooves define raised elements (blocks, ribs), thereby creating edge corners and voids in the material. These grooves represent void volumes, which, in this application, are expressed as a percentage of the total tread volume (including the volume of the raised elements and the volume of all grooves) by a term called the "void-to-volume ratio." A void-to-volume ratio of zero indicates that the tread has no grooves or voids.
[0089] This invention is particularly suitable for the tread of tires intended for installation on vehicles that travel on non-asphalt surfaces (referred to as "off-road" vehicles). Preferably, the tires are tires for off-road vehicles selected from construction site vehicles, agricultural vehicles, and heavy vehicles, more particularly construction site vehicles whose tires are subjected to very specific stresses, especially on stony surfaces. Therefore, advantageously, pneumatic or non-pneumatic tires with a tread comprising the composition according to the invention are tires for construction site vehicles, agricultural vehicles, or heavy vehicles, preferably construction site vehicles. These tires have a tread with a greater thickness of rubber material compared to the tread thickness of tires for light vehicles (particularly passenger cars or trucks). Typically, the wear portion of the tread for heavy vehicle tires is at least 15 mm thick, and the wear portion of the tread for construction site vehicle tires is at least 30 mm, or even up to 120 mm. Therefore, the tread of the tire according to the invention advantageously has one or more grooves with an average depth ranging from 15 mm to 120 mm, preferably 65 mm to 120 mm.
[0090] The diameter of the pneumatic tire according to the invention can be from 20 inches to 63 inches, preferably from 35 inches to 63 inches.
[0091] Furthermore, the average volumetric void ratio can be in the range of 5% to 40%, preferably 5% to 25%, over the entire tread of the tire according to the invention.
[0092] Another subject of the present invention is a rubber track comprising at least one rubber element comprising a composition according to the present invention, wherein the at least one rubber element is preferably an annular rubber belt or a plurality of rubber pads.
[0093] The present invention relates to the above-mentioned rubber articles in the green state (i.e. before curing) and in the cured state (i.e. after cross-linking or vulcanization).
[0094] Preparation of III-7 Rubber Composition
[0095] The composition according to the invention is prepared by using two consecutive preparation stages known to those skilled in the art in a suitable mixer:
[0096] - The first stage of thermomechanical processing or kneading (“non-production” stage), which can be carried out in a single thermomechanical step, during which all necessary components (particularly the elastomer matrix, reinforcing fillers, and optional various other additives) except for the crosslinking system are introduced into a suitable mixer (e.g., a standard closed mixer (e.g., a Banbury type)). During thermomechanical kneading, optional fillers can be introduced into the elastomer in one or multiple batches. Where the filler has been wholly or partially introduced into the elastomer in masterbatch form (e.g., as described in patent applications WO 97 / 36724 or WO 99 / 16600), what is introduced is the directly kneaded masterbatch, other elastomers or fillers not present in the composition in masterbatch form (where appropriate), and optional various other additives besides the crosslinking system. The non-production stage can be carried out at high temperatures, with a maximum temperature between 110°C and 200°C, preferably between 130°C and 185°C, and a duration typically between 2 and 10 minutes.
[0097] - After the mixture obtained in the non-production first stage is cooled to a lower temperature (typically below 120°C, for example, between 40°C and 100°C), a second stage of machining (“production” stage) is carried out in an open mixer (e.g., a two-roll mill). The crosslinking system is then introduced, and the combined mixture is mixed for several minutes, for example, between 5 and 15 minutes.
[0098] These stages have been described, for example, in patent applications EP-A-0501227, EP-A-0735088, EP-A-0810258, WO 00 / 05300, or WO 00 / 05301.
[0099] The resulting final composition is then calendered, for example, in the form of sheets or plates (particularly for laboratory characterization), or extruded (or co-extruded with another rubber composition) in the form of a rubber semi-finished product (or molding element) that can be used, for example, as a conveyor belt support layer. Conveyor belts can then be manufactured using these products according to techniques known to those skilled in the art.
[0100] The composition can be in a green state (before crosslinking or vulcanization) or in a cured state (after crosslinking or vulcanization).
[0101] The crosslinking of the composition can be carried out in a manner known to those skilled in the art, for example at temperatures and pressures between 130°C and 200°C.
[0102] IV - Preferred Implementation
[0103] Based on the above description, preferred embodiments of the present invention are described as follows:
[0104] 1. A rubber composition, said rubber composition being based at least on 10 phr to 90 phr of styrene-butadiene rubber and 10 phr to 90 phr of a copolymer of ethylene and 1,3-diene, reinforcing fillers and a crosslinking system, wherein the ethylene units in the copolymer of ethylene and 1,3-diene account for more than 50 moles of the monomer units of the copolymer of ethylene and 1,3-diene.
[0105] 2. The rubber composition according to embodiment 1, wherein the ethylene units in the copolymer of ethylene and 1,3-diene account for between 50 mol% and 95 mol% of the monomer units of the copolymer of ethylene and 1,3-diene.
[0106] 3. The rubber composition according to any of the foregoing embodiments, wherein the 1,3-diene is 1,3-butadiene.
[0107] 4. The rubber composition according to any of the foregoing embodiments, wherein the copolymer of ethylene and 1,3-diene comprises units of formula (I) or units of formula (II), or comprises units of formula (I) and units of formula (II).
[0108]
[0109] -CH2-CH(CH=CH2)- (II).
[0110] 5. The rubber composition according to embodiment 4, wherein the mole percentages (o and p, respectively) of the unit of formula (I) and the unit of formula (II) in the copolymer of ethylene and 1,3-diene satisfy the following equation (Equation 1), preferably satisfy the equation (Equation 2), wherein o and p are calculated based on the monomer units of the copolymer of ethylene and 1,3-diene,
[0111] 0<o+p≤25 (Equation 1)
[0112] 0<o+p<20 (Equation 2).
[0113] 6. The rubber composition according to any one of the preceding embodiments, wherein the crystallinity of the copolymer is less than 20%, preferably less than 15%, more preferably less than 10%.
[0114] 7. The rubber composition according to any one of the preceding embodiments, wherein the copolymer of ethylene and 1,3-diene is a random copolymer.
[0115] 8. The rubber composition according to any one of the preceding embodiments, wherein the content of the copolymer of ethylene and 1,3-diene units is in the range of 20 phr to 80 phr, preferably 30 phr to 70 phr.
[0116] 9. The rubber composition according to any one of the preceding embodiments, wherein the content of styrene-butadiene rubber is in the range of 20 phr to 80 phr, preferably 30 phr to 70 phr.
[0117] 10. The rubber composition according to any one of the preceding embodiments, wherein the sum of the content of the copolymer of ethylene and 1,3-diene and the content of styrene-butadiene rubber is greater than 75 phr, preferably greater than 90 phr.
[0118] 11. The rubber composition according to any one of the preceding embodiments, wherein the reinforcing filler comprises carbon black, silica or a mixture thereof.
[0119] 12. The rubber composition according to any one of the preceding embodiments, wherein the reinforcing filler comprises greater than 50% by weight, preferably greater than 80% by weight of carbon black.
[0120] 13. The rubber composition according to any one of the preceding embodiments, wherein the reinforcing filler consists only of carbon black.
[0121] 14. The rubber composition according to any one of embodiments 11 to 13, wherein the reinforcing filler comprises greater than 50% by weight of at least one carbon black, and the carbon black has a BET specific surface area of 60 m 2 / g to 160 m 2 / g, preferably 70m 2 / g to 130m 2 Within the range of / g.
[0122] 15. The rubber composition according to any of the foregoing embodiments, wherein the content of reinforcing filler is in the range of 10 phr to less than 100 phr, preferably 15 phr to 90 phr.
[0123] 16. The rubber composition according to any one of embodiments 1 to 14, wherein the content of reinforcing filler is in the range of 10 phr to less than 49 phr, preferably 15 phr to 48 phr, and more preferably 20 phr to 47 phr.
[0124] 17. The rubber composition according to any of the foregoing embodiments, wherein the volume fraction of the filler is less than 19%, preferably in the range of 10% to less than 19%.
[0125] 18. The rubber composition according to any of the foregoing embodiments, wherein the composition does not contain any hydrocarbon plasticizer, or contains less than 10 phr, preferably less than 5 phr, of hydrocarbon plasticizer.
[0126] 19. The rubber composition according to any of the foregoing embodiments, wherein the composition does not contain any hydrocarbon plasticizer resin.
[0127] 20. The rubber composition according to any of the foregoing embodiments, wherein the composition does not contain a plasticizer that is liquid at 23°C, or contains a plasticizer that is liquid at 23°C with less than 40 phr, preferably less than 30 phr.
[0128] 21. The rubber composition according to any one of embodiments 1 to 19, wherein the composition contains a plasticizer that is liquid at 23°C, preferably in a content of 0 phr to less than 40 phr, more preferably in the range of 2 phr to 30 phr.
[0129] 22. The rubber composition according to embodiment 20 or 21, wherein the plasticizer, which is liquid at 23°C, is selected from naphthenic oils, paraffin oils, MES oils, TDAE oils, RAE oils, TRAE oils, SRAE oils, mineral oils, vegetable oils, ether plasticizers, ester plasticizers, phosphate plasticizers, sulfonate plasticizers, and mixtures thereof.
[0130] 23. The rubber composition according to embodiment 20 or 21, wherein the plasticizer, which is liquid at 23°C, is selected from MES oil, TDAE oil, naphthenic oil, vegetable oil, and mixtures thereof.
[0131] 24. The rubber composition according to any of the foregoing embodiments, wherein the crosslinking system is a vulcanization system based on molecular sulfur and / or based on a sulfur donor.
[0132] 25. A rubber article comprising a composition as defined in any one of embodiments 1 to 24, wherein the article is preferably selected from pneumatic tires, non-pneumatic tires, tracks, and conveyor belts.
[0133] 26. A conveyor belt (1) comprising a support layer (2), a reinforcement layer (3) and a drive layer (4), wherein the support layer (2) is composed of a rubber composition as defined in any one of embodiments 1 to 24.
[0134] 27. A track comprising at least one rubber element comprising a composition as defined in any one of embodiments 1 to 24.
[0135] 28. The track according to embodiment 27, wherein at least one rubber element is an annular rubber belt or a plurality of rubber pads.
[0136] 29. A pneumatic or non-pneumatic tire having a tread comprising a composition as defined in any one of embodiments 1 to 24, the tire being a tire for an off-road vehicle selected from construction site vehicles, agricultural vehicles, or heavy vehicles, preferably construction site vehicles.
[0137] 30. The tire according to embodiment 29, wherein the tire tread has one or more grooves, the average depth of which is in the range of 30 mm to 120 mm, preferably 45 mm to 75 mm.
[0138] 31. The tire according to any one of embodiments 29 to 30, wherein the average volumetric void ratio of the tire over the entire tread is in the range of 5% to 40%, preferably 5% to 25%.
[0139] 32. The tire according to any one of embodiments 29 to 31, wherein the diameter of the tire is in the range of 20 inches to 63 inches, preferably 35 inches to 63 inches.
[0140] IV-Example
[0141] Measurements and tests used in IV-1
[0142] IV-1.1 Determination of the microstructure of elastomers:
[0143] pass 1 H NMR analysis was used to determine the microstructure, when 1 When the resolution of H NMR spectra cannot be assigned and quantified for all species, combined with 13C10 NMR analysis was performed using a Bruker 500MHz NMR spectrometer at frequencies of 500.43MHz for proton observation and 125.83MHz for carbon observation. For insoluble elastomers capable of swelling in solvents, protons and carbon were observed in proton-decoupled mode using a 4mm z-class HRMAS probe. Spectra were acquired at rotation speeds from 4000Hz to 5000Hz. For measurements of soluble elastomers, protons and carbon were observed in proton-decoupled mode using a liquid NMR probe. Insoluble samples were prepared in a rotor filled with the analyzed material and a deuterated solvent (typically deuterated chloroform (CDCl3)) that allows swelling. The solvent used must always be deuterated, and its chemical properties can be adjusted by those skilled in the art. The amount of material used was adjusted to obtain spectra with sufficient sensitivity and resolution. Soluble samples are dissolved in a deuterated solvent (typically deuterated chloroform (CDCl3)) (approximately 25 mg of elastomer per ml). The solvent or solvent blend used must always be deuterated, and its chemical properties can be adjusted by someone skilled in the art. In both cases (soluble or swollen samples): For proton NMR, a simple 30° pulse sequence is used. The spectral window is adjusted to observe all resonance lines belonging to the analyte. The accumulation number is set to obtain a signal-to-noise ratio sufficient for quantification of each unit. The cycle delay between each two pulses is adjusted for quantitative measurement. For carbon NMR, a single 30° pulse sequence is used, with proton decoupling performed only during acquisition to avoid the nuclear Overhouse effect (NOE) and maintain quantification. The spectral window is adjusted to observe all resonance lines belonging to the analyte. The accumulation number is set to obtain a signal-to-noise ratio sufficient for quantification of each unit. The cycle delay between each two pulses is adjusted for quantitative measurement. NMR measurements are performed at 25°C.
[0144] IV-1.2 Determination of the macroscopic structure of polymers by size exclusion chromatography (SEC):
[0145] a) Measurement principle:
[0146] Size exclusion chromatography, or SEC, separates macromolecules in solution based on their size by using a column packed with porous gel. Macromolecules are separated based on their hydrodynamic volume, with the largest macromolecules eluting first.
[0147] Combined with a triple detector (3D) (refractive meter, viscometer, and 90° light scattering detector), SEC can determine the distribution of absolute molar mass of polymers. It can also calculate individual number-average absolute molar mass (Mn) and weight-average absolute molar mass (Mw), as well as dispersibility.
[0148] b) Polymer preparation:
[0149] Each sample was dissolved in tetrahydrofuran at a concentration of approximately 1 g / L. The solution was then filtered through a filter with a porosity of 0.45 μm prior to injection.
[0150] c) 3D SEC Analysis:
[0151] The number-average molar mass (Mn), weight-average molar mass (Mw), and polydispersity index (Ip) of copolymers of ethylene and 1,3-diene (hereinafter referred to as the sample) were determined in an absolute manner by triple detection size exclusion chromatography (SEC). The advantage of triple detection size exclusion chromatography is that it directly measures the average molar mass without calibration.
[0152] The refractive index increment dn / dc of a sample solution is measured online using the peak area detected by a refractometer (RI) of a liquid chromatography apparatus. For this method to be applied, it must be validated that 100% sample mass is injected and eluted through the column. The area of the RI peak depends on the sample concentration, the RI detector constant, and the dn / dc value.
[0153] To determine the average molar mass, a pre-prepared and filtered 1 g / L solution was injected into the chromatographic system. A Waters Alliance line was used. The eluent was tetrahydrofuran containing 250 ppm BHT (2,6-di(tert-butyl)-4-hydroxytoluene), and the flow rate was 1 mL / min. -1 The system temperature was 35℃, and the analysis time was 60 min. A set of three Agilent columns, commercially available as PL Gel Mixed B LS, was used. The sample solution injection volume was 100 μl. The detection system consisted of a Wyatt differential viscometer (commercially known as Viscostar II), a Wyatt differential refractometer (commercially known as Optilab T-Rex with a wavelength of 658 nm), and a Wyatt multi-angle static light scattering detector (commercially known as Dawn Heleos 8+ with a wavelength of 658 nm).
[0154] To calculate the number-average molar mass and polydispersity index, the refractive index increment dn / dc of the sample solution obtained above was integrated. The software used to evaluate the chromatographic data was the Astra system from Wyatt.
[0155] Mn, Mw, and Ip of styrene-butadiene rubber were obtained by size exclusion chromatography (SEC) using tetrahydrofuran (THF) as eluent at a rate of 1 ml / min. The molar mass was 1200 g·mol⁻¹. -1 and 512800g.mol -1The polystyrene (PS) standard was used for calibration. The SEC chain was equipped with an RI Waters 2414 detector and a set of two temperature-controlled columns (Shodex KF-802.5 and KF-804) at 35°C.
[0156] IV-1.3 Crystallinity Determination
[0157] Crystallinity was measured by measuring the enthalpy of melting observed in the copolymer of ethylene and 1,3-diene. This endothermic phenomenon was observed during the analysis of the thermogram measured by DSC (differential scanning calorimetry). Measurements were performed under an inert (helium) atmosphere with repeated scans from -150°C to 200°C at a gradient of 20°C / min.
[0158] The signal corresponding to the endothermic (melting) phenomenon is integrated, and the crystallinity is the ratio of the measured enthalpy to the enthalpy of fully crystalline polyethylene (290 J / g).
[0159] % crystallinity = (measured enthalpy (in J / g)) / (theoretical enthalpy (in J / g) of 100% crystallized polyethylene).
[0160] Abrasion resistance after IV-1.4 curing
[0161] Abrasion resistance was measured on a drum at 23°C according to standard ISO 4649 (2017).
[0162] The volume of rubber lost during the test is expressed in mm. 3 This indicates that the smaller the volume, the better the wear resistance.
[0163] Dynamic properties of IV-1.5 after curing: tensile test
[0164] These tensile tests determine elastic stress and fracture properties. Unless otherwise stated, these tests are performed according to French Standard NF T 46-002 of September 1988. Processing the tensile records also allows for plotting the modulus as a function of elongation. The modulus used in this paper is the nominal (or apparent) secant modulus measured during the first elongation, calculated by normalizing to the initial cross-section of the specimen.
[0165] Elongation at break (EB%) was tested on H2 dumbbell-shaped specimens based on standard NF ISO 37 of December 2005, and measured at a tensile speed of 500 mm / min. Elongation at break is expressed as % elongation. Breaking stress is expressed in MPa.
[0166] All these tensile measurements were performed under standard conditions of temperature (23±2℃) and humidity (50±5% relative humidity) according to French standard NF T 40-101 (December 1979).
[0167] Measurements were performed on cross-linked samples, which were optionally subjected to an aging process in an oven at 140°C for 48 h, 96 h, 120 h, or 168 h.
[0168] Results are given relative to the control, with a base of 100. Results greater than 100 indicate an increase in the value under consideration, i.e., an improvement in elongation at break.
[0169] Resistance to fatigue crack propagation (DeMattia fatigue) after IV-1.6 curing
[0170] Resistance to DeMattia fatigue was determined using the "crack propagation" method according to French standard ISO 132.
[0171] The retrieved data represents the number of cycles required to extend the gap from L0mm to (L0+2)mm, from L0mm to (L0+6)mm, and from L0mm to (L0+10)mm.
[0172] The higher the number of cycles, the better the fatigue resistance of the composition under consideration.
[0173] Synthesis of IV-2 polymer
[0174] In the synthesis of polymers, all reactants except metallocenes are commercially available. Butyloctylmagnesium (BOMAG) (20% in heptane, C = 0.88 mol / L) -1 The ethylene (N35 grade) is from Chemitura and stored in Schlenk tubes under an inert atmosphere. It is ready to use without purification.
[0175] Ethylene-1,3-butadiene copolymer: Elastomer E1 synthesized according to the steps described below (according to the present invention).
[0176] Butyloctylmagnesium (BOMAG) was added to a reactor containing methylcyclohexane, ethylene (Et), and butadiene (Bd) in the proportions shown in Table 1 at 80°C to neutralize impurities in the reactor, followed by the addition of a catalyst system (see Table 1). The reaction temperature was then adjusted to 80°C, and polymerization began. The polymerization was carried out at a constant pressure of 8 bar. Throughout the polymerization process, ethylene and butadiene (Bd) were fed into the reactor in the proportions specified in Table 1. The polymerization was terminated by cooling, reactor degassing, and the addition of ethanol. An antioxidant was added to the polymer solution. The copolymer was recovered by drying to a constant mass in an oven under vacuum. The catalyst system was a pre-formed catalyst system. It was prepared in methylcyclohexane using a metallocene [Me₂SiFlu₂Nd(μ-BH₄)₂Li(THF)], the co-catalyst butyloctylmagnesium (BOMAG), and the pre-formed monomer 1,3-butadiene in the amounts shown in Table 4. It is prepared according to the preparation method in Section II.1 of patent application WO 2017 / 093654A1.
[0177] Tables 2 and 3 show the microstructure and properties of copolymer E1. For the microstructure, Table 2 shows the molar ratios of ethylene (Eth) units, 1,3-butadiene units, and 1,2-cyclohexanediyl (cyclic) units.
[0178] [Table 1]
[0179] Metallocene concentration (mmol / L) 0.07 Alkylating agent concentration (mmol / L) 0.33 pre-formed monomer / Nd metal molar ratio 90 Feed composition (mol% Et / Bd) 80 / 20
[0180] [Table 2]
[0181] Et (mol%) 79 Bd (moles%) 14 1,2-Cyclohexanediyl (mol%) 7
[0182] [Table 3]
[0183] Tg (°C) -41 Mn(g / mol) 130700
[0184] Preparation of IV-3 Composition
[0185] In the following examples, the rubber composition was prepared as described in point III.7 above. Specifically, the "non-production" stage was carried out for 5.5 minutes in a 3-liter mixer with an average blade speed of 60 rpm until the maximum discharge temperature of 160°C was reached. The "production" stage was carried out for 3.5 minutes in a 3-liter mixer with an average blade speed of 30 rpm until the maximum discharge temperature of 90°C was reached.
[0186] The composition is crosslinked under pressure at a temperature between 130°C and 200°C in a manner known to those skilled in the art.
[0187] Testing of IV-4 rubber compositions
[0188] The examples shown below are intended to compare the performance trade-offs between crack propagation resistance and elongation at break, as well as the retention of elongation at break over time, of the composition (C1) according to the invention and the control composition (T1).
[0189] The difference between composition C1 and composition T1 lies in the characteristics of the second copolymer present in the elastomer matrix, which coexists with the butadiene-styrene copolymer. Since the elastomer in composition T1 is increased using a liquid plasticizer, a corresponding amount of liquid plasticizer is added to composition C1.
[0190] Table 4 shows the tested compositions (in phr), and Table 5 shows the results obtained.
[0191] [Table 4]
[0192] SBR(1) 70 70 EPDM(2) 34.5 - EBR(3) - 30 Liquid plasticizers (4) 4.5 Carbon black (5) 45 45 Anti-ozone wax (6) 2.5 2.5 Antioxidants (7) 3 3 TMQ(8) 3 3 stearic acid 1 1 ZnO(9) 5 5 sulfur 1.2 1.2 Accelerator (10) 1.4 1.4
[0193] (1) ESBR “KER1502” from Synthos
[0194] (2) EPDM sold by ExxonMobil under the name "Vistalon 8800", which uses 15% by weight of oil (i.e., 4.5 phr in composition T1) in increments and has 54% by weight of ethylene and 10% by weight of norbornene.
[0195] (3) The elastomer E1 prepared above: an elastomer containing 79 mol% ethylene units, 7 mol% 1,2-cyclohexanediyl units, 8 mol% 1,2-units and 6 mol% 1,4-units.
[0196] (4) "Primol 352" liquid plasticizer from ExxonMobil
[0197] (5) N234 grade carbon black according to standard ASTM D-1765
[0198] (6) Anti-ozone wax, Varazon 4959 from Sasol Wax
[0199] (7) N-(1,3-dimethylbutyl)-N-phenyl-p-phenylenediamine, from Flexsys' Santoflex 6-PPD
[0200] (8) 2,2,4-trimethyl-1,2-dihydroquinoline from Flexys
[0201] (9) Industrial-grade zinc oxide from Umicore
[0202] (10) N-(tert-butyl)-2-benzothiazole sulfenamide, from Santocure TBBS of Flexsys
[0203] [Table 5]
[0204] DeMattia fatigue L+2 (thousand cycles) 2006 3330 DeMattia fatigue L+6 (thousand cycles) 5850 10000 DeMattia fatigue L+10 (thousand cycles) 12083 24786 Initial EB (%) (Base 100) 100 112 EB (%) 48h 140℃ (baseline 100) 100 116 EB (%) 96h 140℃ (baseline 100) 100 150 EB (%) 120h 140℃ (baseline 100) 100 181 EB (%) 168h 140℃ (baseline 100) 100 1540
[0205] The results shown in Table 5 above demonstrate that using the ethylene-1,3-diene copolymer according to the invention instead of prior art EPDM improves the crack propagation resistance and mechanical properties of rubber compositions containing butadiene-styrene copolymers. In particular, it was observed that the elongation at break properties of the compositions according to the invention are more effectively maintained over time compared to the control compositions. Finally, the applicant observed that the aforementioned improvements in properties are achieved while maintaining acceptable or even unchanged abrasion resistance compared to the control compositions.
[0206] Therefore, the compositions according to the invention are particularly advantageous for forming various rubber products, such as conveyor belts.
Claims
1. A rubber composition, said rubber composition being based at least on a styrene-butadiene rubber of 10 phr to 90 phr and a copolymer of ethylene and 1,3-diene of 10 phr to 90 phr, reinforcing fillers, and a crosslinking system, wherein the ethylene units in said copolymer account for more than 50 mol% of the monomer units of the copolymer, wherein, The ethylene units in the copolymer account for between 50 mol% and 95 mol% of the monomer units of the copolymer; 1,3-Diene is 1,3-butadiene; The copolymer comprises units of formula (I) and units of formula (II). (I) -CH2-CH(CH=CH2)-(II); The copolymer has a crystallinity of less than 20%; and The copolymer of ethylene and 1,3-diene is a random copolymer.
2. The rubber composition according to claim 1, wherein, The content of the copolymer of ethylene and 1,3-diene is in the range of 20 phr to 80 phr, and the content of styrene-butadiene rubber is in the range of 20 phr to 80 phr.
3. The rubber composition according to claim 1, wherein, The total content of the copolymer of ethylene and 1,3-diene and the content of styrene-butadiene rubber is greater than 75 phr.
4. The rubber composition according to claim 1, wherein, The reinforcing filler includes carbon black, silica, or a mixture thereof.
5. The rubber composition according to claim 1, wherein the composition does not contain any hydrocarbon plasticizer, or contains less than 10 phr of hydrocarbon plasticizer.
6. The rubber composition according to any one of claims 1 to 4, wherein the composition comprises 23 o C represents a liquid plasticizer.
7. The rubber composition according to claim 6, wherein, In 23 o C represents liquid plasticizers selected from mineral oils, vegetable oils, ether plasticizers, ester plasticizers, and mixtures thereof.
8. The rubber composition according to claim 6, wherein, In 23 o The plasticizers listed under C that are liquids are selected from naphthenic oils, paraffin oils, MES oils, TDAE oils, and RAE oils.
9. The rubber composition according to claim 6, wherein, In 23 o The plasticizers listed under C that are liquids are selected from TRAE oil and SRAE oil.
10. The rubber composition according to claim 6, wherein, In 23 o The plasticizers listed under C that are liquids are selected from phosphate ester plasticizers and sulfonate ester plasticizers.
11. The rubber composition according to claim 1, wherein, The crosslinking system is a vulcanization system based on molecular sulfur and / or based on sulfur donor.
12. A rubber article comprising a rubber composition as defined in any one of claims 1 to 11.
13. A conveyor belt (1) comprising a support layer (2), a reinforcement layer (3) and a drive layer (4), wherein the support layer (2) is composed of a rubber composition as defined in any one of claims 1 to 11.
Citation Information
Patent Citations
Rubber compound and tires based on such a compound
EP0501227A1
Rubber composition suitable for treads containing aluminium doped precipitated silica
EP0735088A1
Diene rubber composition containing alumina as reinforcing filler and use in tire treads
EP0810258A1
Catalytic system, process for its preparation and that of an ethylene-conjugated diene copolymer
EP1092731A1
Novel elastomer composites, method and apparatus
WO1997036724A2